EXERT and TEAM 21: Partnership for Professional Development - Judlth Adkison; William E. Camp; Bruce Meeks (Educational Considerations, 1988)
Superintendents and principals need a location and time for professional development. EXERT and TEAM 21 are examples of cooperative school/business/university partnerships which have provided new ways to meet these needs.